Sexual symbolism in the Early Neolithic of the Southern Levant - Mithen, Steven (Documenta Praehistorica, 2005)
WF16 is a Pre-Pottery Neolithic site in the Southern Levant that has produced an important collection of ground stone artefacts. These include one explicit and one ambiguous representation of a phallus - the latter may be a human head and shoulders. The authors note the visual similarity of certain pestles from WF16 to phalli and suggest that such artefacts and their use may have been imbued with sexual metaphor. As such, the most potent references to sex, reproduction and fertility in the early Neolithic may not be the exotic figures claimed to be 'Mother Goddesses' but located in the most mundane of domestic artefacts.
Keywords: Levant; arheološke najdbe; neolitik; artefakti; spolnost; sexual intercourse; simboli; symbol